The Battle for God : Fundamentalism in Judaism, Christianity and Islam - Armstrong, Karen (London HarperCollins Publishers, 2001)
One of the most potent forces bedevilling the modern world is religious extremism. The need to understand it has never been greater, and Karen Armstrong attempts to do so in this text.
Include Glossary, Notes, Bibliography and Index.
Britain's greatest religious historian chronicles the rise and rise of fundamentalism.
Keywords: Religious fundamentalism -- Islamic fundamentalism -- Orthodox Judaism -- Fundamentalism -- Israel -- Judaism -- Church history--Modern period -- Islam